Design and fabrication of portable notebook table - Mohd Amir, Zaini Naziff (2008)
'Portable Notebook Table' is an equipment that are use with notebook as a table.The fabrication of this product started with surveying in market about the product,specification analysis, concept designing, detail concept designing and fabrication of the product. Four (4) products were selected from the market for the analysis and investigation. Several concepts has been done and one of these concepts that is simple and portable has been choose to fabricate. The investigation was made in scope of the constraint that may occur for the development of the product and relevance of the product manufacturing processes. This product have been fabricate according to engineering method through many fabrication process such as welding, cutting, drilling and assembling. For development of this project and future works, some suggestion was made for upgrading the product. Result of the fabrication has been tested and analyze and it shows that it can support the weight of all types of notebook existed in market.The criteria of this product which is easy to carry to any places with comfort satisfied the problems for existing products in the market.